External carotid artery embolus with internal carotid artery occlusion with acute ischemic stroke: predictor of cardioembolic etiology. (23rd June 2011) - Tomsick, Thomas; Thangasamy, Senthur; Stamatis, Thomas; Khatri, Pooja; Broderick, Joseph
Abstract : Arteriograms performed in the Interventional Management of Stroke studies were analyzed for external carotid artery embolus. Two cases were identified and diagnosed as thromboembolic due to a cardiac origin. This is an uncommon but useful finding on angiography which is helpful for further management. It is hypothesized that finding embolus within the external carotid artery on angiography in stroke patients with internal carotid artery occlusion allows confident ascription to a proximal, usually cardiac, source.